2017
DOI: 10.1002/2017jd027235
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recent Local Moisture Recycling on the Northwestern Tibetan Plateau Deduced From Ice Core Deuterium Excess Records

Abstract: Local moisture recycling plays an essential role in maintaining an active hydrological cycle of the Tibetan Plateau (TP). Previous studies were largely limited to the seasonal time scale due to short and sparse observations, especially for the northwestern TP. In this study, we used a two‐component mixing model to estimate local moisture recycling over the past decades from the deuterium excess records of two ice cores (i.e., Chongce and Zangser Kangri) from the northwestern TP. The results show that on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 77 publications
(145 reference statements)
3
40
0
1
Order By: Relevance
“…Temporal records from ice cores in Asia go back 10 s to 100 s of years, and show seasonal variability in d-excess, where high values are associated with Mediterranean-derived moisture and/or continental recycling, and low values are associated with Indian or Arctic Ocean-derived moisture and/or arid conditions that promote subcloud evaporation [5,50,51]. Because falling snow at high elevations does not evaporate much due to cold temperatures and a cloud base that is relatively close to the ground, seasonal changes in d-excess are more likely controlled by distinct moisture sources (oceanic and continental), as opposed to variations in subcloud evaporation.…”
Section: Interpreting Paleoclimate From Deuterium Excessmentioning
confidence: 99%
“…Temporal records from ice cores in Asia go back 10 s to 100 s of years, and show seasonal variability in d-excess, where high values are associated with Mediterranean-derived moisture and/or continental recycling, and low values are associated with Indian or Arctic Ocean-derived moisture and/or arid conditions that promote subcloud evaporation [5,50,51]. Because falling snow at high elevations does not evaporate much due to cold temperatures and a cloud base that is relatively close to the ground, seasonal changes in d-excess are more likely controlled by distinct moisture sources (oceanic and continental), as opposed to variations in subcloud evaporation.…”
Section: Interpreting Paleoclimate From Deuterium Excessmentioning
confidence: 99%
“…Similar results were also found in the northwestern QTP (6,100 m a.s.l.) by An et al (2017). Froehlich et al (2008) confirmed that the impact of subcloud evaporation on d‐excess of precipitation could be ignored in the high elevation regions due to the shorter distance between the ground and cloud base.…”
Section: Methodsmentioning
confidence: 93%
“…Notably, the latter two areas had the lowest ratios on the QTP among existing results. Based on the ice core records at Chongce and Zangser Kangri, An et al (2017) found the moisture recycling ratio were 15% ‐ 82.6% from 1979 to 2012 and 24.7% ‐ 81.6% from 1979 to 2008, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…使 用 Picarro L2120-i液 态 水 同位 素分析仪对58.8和135.8 m崇测冰芯进 行了稳定同位素分析, 样品δ 18 O的分 析精度小于0.1‰ [12] . 58.8 m崇测冰芯 共采集了1956个样品, 采样分辨率为 2~3 cm/样品 [13] ; 135.8 m崇测冰芯从…”
unclassified